2020
DOI: 10.1007/s10557-020-07088-5
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 Analog Liraglutide Attenuates Pressure-Overload Induced Cardiac Hypertrophy and Apoptosis through Activating ATP Sensitive Potassium Channels

Abstract: Purpose This study aimed to investigate whether inhibition of glucagon-like peptide-1 (GLP-1) on pressure overload induced cardiac hypertrophy and apoptosis is related to activation of ATP sensitive potassium (KATP) channels. Methods Male SD rats were randomly divided into five groups: sham, control (abdominal aortic constriction), GLP-1 analog liraglutide (0.3 mg/kg/twice day), KATP channel blocker glibenclamide (5 mg/kg/day), and liraglutide plus glibenclamide.Results Relative to the control on week 16, lira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Moreover, GLP-1R activation counteracts the effects of β-adrenoceptor stimulation on cardiac ventricular excitability and reduces ventricular arrhythmic potential [165]. Apart from maintaining calcium channel homeostasis, GLP-1RAs also activate ATPsensitive potassium channels to attenuate cardiac apoptosis and hypertrophy induced by pressure overload [166].…”
Section: Improving Cardiomyocyte/cardiac Fibroblast Dysfunction By Glp-1rasmentioning
confidence: 99%
“…Moreover, GLP-1R activation counteracts the effects of β-adrenoceptor stimulation on cardiac ventricular excitability and reduces ventricular arrhythmic potential [165]. Apart from maintaining calcium channel homeostasis, GLP-1RAs also activate ATPsensitive potassium channels to attenuate cardiac apoptosis and hypertrophy induced by pressure overload [166].…”
Section: Improving Cardiomyocyte/cardiac Fibroblast Dysfunction By Glp-1rasmentioning
confidence: 99%
“…Supporting these statements, there are some in vitro and in vivo studies performed with GLP-1R agonists, which are providing further novel information at cellular levels. 7,9,19,22 In that line, recent studies demonstrated that a GLP-1R agonist, liraglutide protects cardiomyocytes from metabolic disturbance and mitochondrial dysfunction. 6,23 This agonist also regulates Ca 2+ -homeostasis, the electrophysiological activities of cardiomyocytes modulating Ca 2+ -handling proteins, 2,7 reduces ventricular arrhythmic potential, 8 and activates ATP-sensitive K + -channels.…”
Section: Introductionmentioning
confidence: 97%
“…[3][4][5] Interestingly, these agonists have a wide range of pleiotropic effects on the cardiovascular system, independent of the above effects. [6][7][8] In that regard, it has been shown with experimental studies on GLP-1R benefits in cardiomyocytes, 2,[6][7][8][9] and clinical outcomes on cardiovascular system abnormalities with their varied efficacy. [10][11][12][13][14][15] Physiologically, GLP-1 in the heart can drive myocardial glucose uptake and thereby provide protection against pathological stimuli such as myocardial ischaemic-injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins were extracted from rabbit atria tissue specimens or HL-1 cells. The protein content was determined by using the Bradford method according to our previous study [19] . The same amount of protein (40μg) was loaded per lane and separated by 8-12% sodium dodecy1 sulfate-polyacrylamide gel electrophoresis.…”
Section: Western Blottingmentioning
confidence: 99%